Edukasi Komunikasi Keluarga di Era Digital sebagai Upaya Pencegahan Perceraian di Kabupaten Subang Utara - Pranawukir, Iswahyu; Misnan, Misnan; Sukma, Agus Hitopa; Riyantie, Mayang; Romli, Romli (Yayasan Kawanad, 2025)
The community service activity aims to enhance knowledge, awareness, and family communication skills in the digital era among residents of Rancabango Village, North Subang. The activity began with a pre-test questionnaire to measure participants' initial understanding of verbal and nonverbal communication, as well as the utilization of digital media in family interactions. Pre-test results showed that 66% of participants had not yet understood the concept of family communication formally, and only a small portion utilized digital features for emotional communication in daily life. Through a series of interactive counseling sessions, practical training, and simulations (role play), participants were equipped with knowledge and healthy communication skills within the family. Post-activity evaluation through post-test demonstrated significant improvement, with 85% of participants understanding the concept of family communication and being able to recognize the role of verbal and nonverbal language, as well as the impact of gadget use. A total of 76% of participants showed increased emotional awareness toward their partners and children, while 70% were able to apply digital communication techniques such as the use of emoticons and voice messages appropriately. The findings indicate that participatory counseling has proven to have a real impact on forming healthier family communication patterns, while simultaneously playing a role in preventing domestic conflicts and divorce.